Connect with experts and get insightful answers to your questions on IDNLearn.com. Join our Q&A platform to access reliable and detailed answers from experts in various fields.
Sagot :
Step-by-step explanation:
We know that
sin² θ+ cos² θ = 1
¶ cos² θ = 1 - sin² θ
→cos θ × cos θ = (1+sin θ)(1-sin θ)
→cos θ/(1-sin θ) = (1+sin θ)/cos θ
By the property of equal ratio
→cos θ/(1-sin θ) = (1+sin θ)/cos θ =
(1+sin θ-cos θ) /( cos θ- 1+ sin θ)
→cosθ/(1-sinθ) = (1+sinθ-cosθ)/(cosθ- 1+sinθ)
→cosθ/(1-sinθ) = (sinθ-cosθ+1)/(cosθ+sinθ-1)
On dividing LHS by cos θ
→(cos θ/cos θ)/(1- sin θ)/cos θ) =
(sinθ-cosθ+1)/(cosθ+sinθ-1)
→1/(1- sin θ)/cos θ) = (sinθ-cosθ+1)/(cosθ+sinθ-1)
→1/(1/Cos θ)-(Sin θ/ cos θ) =
(sinθ-cosθ+1)/(cosθ+sinθ-1)
→1/(secθ-tanθ) = (sinθ-cosθ+1)/(cosθ+sinθ-1)
→RHS = LHS
Additional comment:
If a/b = c/d then a/b = c/d
= (a+c)/(b+d)
Thank you for being part of this discussion. Keep exploring, asking questions, and sharing your insights with the community. Together, we can find the best solutions. Thank you for trusting IDNLearn.com with your questions. Visit us again for clear, concise, and accurate answers.